2021
DOI: 10.2196/24593
|View full text |Cite
|
Sign up to set email alerts
|

Insights From the SmokeFree.gov Initiative Regarding the Use of Smoking Cessation Digital Platforms During the COVID-19 Pandemic: Cross-sectional Trends Analysis Study

Abstract: Background Smoking is a plausible risk factor for COVID-19 progression and complications. Smoking cessation digital platforms transcend pandemic-driven social distancing and lockdown measures in terms of assisting smokers in their quit attempts. Objective This study aims to examine trends in the number of visitors, followers, and subscribers on smoking cessation digital platforms from January to April 2020 and to compare these traffic data to those obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“… 47 Due to the coronavirus disease 2019 (COVID‐19) pandemic, policy makers should focus more on online methods for smoking cessation interventions in this period or even continue it after easing the lockdown. 48 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 47 Due to the coronavirus disease 2019 (COVID‐19) pandemic, policy makers should focus more on online methods for smoking cessation interventions in this period or even continue it after easing the lockdown. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to these recommended measures, using the Internet is superior to print material and is equivalent to telephone and in‐person counseling 47 . Due to the coronavirus disease 2019 (COVID‐19) pandemic, policy makers should focus more on online methods for smoking cessation interventions in this period or even continue it after easing the lockdown 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate preventive measure against the SARS-CoV-2 infection is smoking cessation (73,74). According to previous research, one-third of smokers were motivated to quit smoking due to the spread of the virus (11).…”
Section: Attitudes Of Subjects About Smoking and Quitting At The Time...mentioning
confidence: 99%
“…This may be attributed to the fact that cessation attempts triggered by the pandemic were largely unaided [ 15 ]. Research in the UK suggests no change in downloads of a popular smoking cessation app during the initial months of the COVID-19 pandemic [ 16 ], though a study in the US from the same time period reported an increase in traffic on the Smokefree website and adult-focused digital intervention platforms in 2020 [ 17 ]. Likewise, research on vaping suggests that a proportion of vapers decreased their product use in the first months of the COVID-19 pandemic (10–24%; [ 10 , 14 ]), though some vapers reported an increase (24–40%; [ 10 , 14 ]), and half did not change their use (50%; [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%